Translation and psychometric evaluation of the Danish version of the knee outcome survey - activities of daily living scale in patients with anterior cruciate ligament injuries - Kamilla Arp; Claus Varnum; Ulrik Dalgas; Bettina Mølri Knudsen; Signe Timm; Bjarke Viberg; Kim Gordon Ingwersen (BMC Musculoskeletal Disorders)
Abstract Background The Knee Outcome Survey – Activities of Daily Living Scale (KOS-ADLS) is a patient-reported outcome measure (PROM) developed to assess symptoms and functional limitations in patients with various knee disorders. The aim of this study was to translate and culturally adapt the KOS-ADLS to Danish and to evaluate the psychometric properties of the Danish version (KOS-ADLS-DK) in patients with anterior cruciate ligament (ACL) injury. Methods The KOS-ADLS was translated and culturally adapted to Danish in accordance with recommended guidelines. To evaluate psychometric properties in a test-retest design 115 Danish patients with ACL injury completed KOS-ADLS-DK and other knee specific PROMs at baseline and after 14 days. A sub-population of 79 patients completed the KOS-ADLS-DK before and after 3 months of rehabilitation. Structural validity (factor analysis), Internal consistency (Cronbach`s alpha), construct validity (hypothesis testing), test-retest reliability (Intraclass Correlation Coefficient [ICC]), test-retest agreement (Bland-Altman plots with 95% Limits of Agreement), Standard Error of Measurement (SEM), Smallest Detectable Chance (SDC), responsiveness (construct approach with hypothesis testing) and floor/ceiling effects were assessed. Results No major problems were revealed in the cross-cultural adaptation process. The KOS-ADLS-DK was uni-dimensional and showed a high internal consistency (Chronbach’s alpha = 0.90). Construct validity was not perfect as only five of seven hypotheses were confirmed, but there was a good reliability (ICC = 0.88) and test-retest agreement showed equal distribution of measurement error across the scale and the SEM was 4.9% and SDC was 13.6%. However, hypotheses testing on change scores revealed the KOS-ADLS-DK to be responsive and there were no floor/ceiling effects. Conclusion Overall, the Danish version of KOS-ADLS is considered a valid, reliable and responsive PROM for assessing symptoms and functional limitations in patients with ACL injury but may show some limitations in its construct validity.